Immunotherapy of Gynaecological High-Risk Human Papilloma Virus Infection With Human Leukocyte Ultrafiltrate - H. Spitzbart; U. B. Hoyme (Hindawi Limited, 2000)
Objective: In this preliminary presentation the outcome of women following systemic treatment of cervical human papilloma virus (HPV) with a leukocyte ultrafiltrate is reported.